Transcatheter Repair in Posterior, Anterior, and Bileaflet Mitral Valve Disease: 1-Year Results From EXPANDed - Kar, Saibal; Price, Matthew J; Morse, M Andrew; Rinaldi, Michael J; Mahoney, Paul; Denti, Paolo; Asch, Federico M; Zamorano, Jose L; Aiyer, Janani; Huang, Rong; Maisano, Francesco; von Bardeleben, Ralph Stephan; et al. (JACC. Cardiovascular interventions, 2025)
Treating anterior and bileaflet mitral valve disease in patients with primary or degenerative mitral regurgitation (DMR) is considered more challenging than posterior leaflet repair. The aim of this analysis was to evaluate the impact of anterior, posterior, or bileaflet disease on outcomes following mitral transcatheter edge-to-edge repair (M-TEER) in the EXPANDed studies. EXPANDed is a pooled, patient-level analysis of subjects undergoing M-TEER with the MitraClip G3 or G4 system as part of the contemporary EXPAND and EXPAND G4 studies. Subjects with DMR were categorized according to echocardiography core laboratory-assessed prolapse or flail location into posterior (prolapse or flail at P1, P2, and/or P3), anterior (prolapse or flail at A1, A2, and/or A3) or bileaflet disease (prolapse or flail at any combination of A1, A2, and A3 and P1, P2, and P3). Key outcomes assessed included procedural outcomes, 30-day major adverse events, and 1-year mitral regurgitation (MR) severity. Of 2,205 subjects in EXPANDed, 556 had echocardiography core laboratory-assessed DMR and prolapse or flail location. A total of 389 had posterior, 106 had anterior, and 61 had bileaflet disease. All groups experienced low device and procedure times with high procedural success rates (defined as discharge MR ≤2+). Thirty-day major adverse events rates were low across all groups (posterior, 4.4% [17 of 388]; anterior, 3.8% [4 of 105]; bileaflet, 6.6% [4 of 61]; P = 0.65). Through 1 year, all groups showed a significant reduction in MR severity from baseline (MR ≤1+ posterior, 82% [179 of 219]; anterior, 93% [53 of 57]; bileaflet, 97% [28 of 29]). Results from the EXPANDed studies demonstrate that subjects with DMR treated with M-TEER experienced significant improvements in outcomes, regardless of the location of prolapse or flail.